Sensing localised corrosion by means of electrochemical noise detection and analysis - Tan, Yong (MDPI Publishing, 2009)
This paper provides a brief review of developments in localised corrosion sensing by means of electrochemical noise detection and analysis. After a bird's eye view of traditional techniques of detecting localised corrosion, electrochemical noise phenomena and methods including noise signatures and noise resistance are briefly reviewed. Noise signatures refer to characteristic patterns in corrosion potential and current fluctuations that are recognised to be indicators of localised corrosion. Noise resistance is defined as the ratio of the standard deviation of potential noise to the standard deviation of current noise that was proposed as a means of determining the rates of general corrosion. The scope of this review is on various forms of electrochemical noise based localised corrosion sensors, with particular focus on an electrochemically integrated multi-electrode array namely the wire beam electrode (WBE). The WBE is a unique localised corrosion sensor that not only detects noise signatures and noise resistance, but also provides unprecedented spatial and temporal information on localised corrosion. Typical experiments are presented to illustrate the applications of WBE sensors.